Local government finance: A systematic literature review using Bibliometrics - Idah, Alma; Bernardianto, R. Biroum; Suffianor, Suffianor (Journal of Science and Education (JSE), 2025)
This study offers a thorough summary of the state of research in the area of local government finance by conducting a systematic literature review. Drawing on 25 years of pertinent publications in the subject of public budgeting and finance, the study addresses a variety of topics, such as capital budgeting, budgeting and budget reform, intergovernmental finance, financial management, and alternative service delivery. Scopus was used to gather the data, and 580 articles were deemed suitable for additional examination. The data were analyzed using Bibliometric approach. The analysis highlights China, the United States, and the United Kingdom as dominant contributors, with a strong focus on topics such as fiscal decentralization, local government finance, and governance efficiency. The author collaboration network reveals fragmented clusters, with limited interconnections among researchers, emphasizing the need for broader global and interdisciplinary collaborations. Additionally, the findings underscore the growing importance of emerging themes such as sustainability, digital governance, and AI-driven fiscal management, which remain underexplored. Geographical imbalances in research output further highlight the need for greater representation from underrepresented regions, including Africa, South America, and parts of Asia. Policymakers and practitioners who want to keep up with the most recent advancements and industry best practices in local government finance will also benefit from it.